Gestão de obras residenciais em condomínio de casas: estudo de caso - Costa, Érica Karine Filgueira (Universidade Federal Rural do Semi-Árido, 2019)
The civil construction represents an important part of the national Brazilian economy that has been growing more moderately over the years. For this reason, attention is turned to building sites in order to increase productivity and sustainability of production. In this context, the main objective of this research is to understand how the planning and management of works in the construction of single-family residences in the city of Mossoró- RN occurs and to identify which measures can be suggested for adequacy, based on the case study of a set of five works of a small construction company. The work was carried out from an exploratory research divided into two stages: theoretical foundation and practical analysis, being the last one composed of an investigation through direct observation and semistructured interview applied to the engineer and the masters of the works. To suggest improvements, we used the examples found in the literature and the empirical experience of those involved. The research highlighted the importance of joining efforts to better organize production on the building site, valuing the planning and control processes, making them indispensable in any work, in order to increase the quality, speed and decrease the costs of works, also improving the work environment, towards the qualification of professionals.
Monografia
Keywords: Gestão; Controle; Planejamento; Pequenas obras; Construtora; Construção Civil; Management; Planning; Control; Construction company; Small works; ENGENHARIAS::ENGENHARIA CIVIL